Self-Compassion Matters: the Relationships Between Perceived Social Support, Self-Compassion, and Subjective Well-Being Among Lgb Individuals in Turkey. - Moe, Jeffry L.; Kemer, Gülşah; Toplu Demirtaş, Ezgi; Pope, Amber L.; Toplu-Demirtas, Ezgi (American Psychological Association, 2018)
Research on the well-being of lesbian, gay, and bisexual (LGB) people has predominately focused on Western (-ized) societies where individualism, and not collectivism, is emphasized. In the present study, we utilized a mediator model via Structural Equation Modeling (SEM) to examine the relationships between self-compassion (i.e., self-kindness, common humanity, and mindfulness), perceived social support (i.e., family, friends, and significant others), and subjective well-being (i.e., life satisfaction, positive affect, and negative affect) in a sample of LGB-identified individuals living in Turkey, a traditionally collectivistic culture (Hofstede, 2001). A sample of 291 LGB individuals (67 lesbian, 128 gay, and 96 bisexual) completed an online survey including the Positive and Negative Affect Schedule, Satisfaction with Life Scale, Multidimensional Scale of Perceived Social Support Scale, and Selfkindness, Common Humanity, and Mindfulness subscales of the Self-Compassion Scale. The results of SEM for the hypothesized mediator model revealed that self-compassion mediated the relationships between perceived social support from family and significant others and subjective well-being, explaining the 77% of the variance in subjective well-being. Implications for the literature base on LGB well-being are discussed, with a focus on the cross-cultural applications.
Keywords: Self-compassion; Collectivistic culture; Gay, and bisexual (lgb) individuals; Lesbian; Socialsupport; Subjective well-being; Social Support; Lesbian, Gay, and Bisexual (LGB) Individuals; And Bisexual (LGB) Individuals; Gay